Clinical Characteristics of Pregnant Women with Covid-19 in Wuhan, China - Chen, Lian; Li, Qin; Zheng, Danni; Jiang, Hai; Wei, Yuan; Zou, Li; Feng, Ling; Xiong, Guoping; Sun, Guoqiang; Wang, Haibo; Zhao, Yangyu; Qiao, Jie (The New England journal of medicine, 2020)
Among 118 pregnant women with Covid-19 in Wuhan, China, the vast majority had a mild course of disease.